Management of tetralogy of Fallot in the pediatric intensive care unit - Hammett, Owen; Griksaitis, Michael J. (Frontiers in Pediatrics, 2023)
Tetralogy of Fallot (ToF) is one of the most common congenital cyanotic heart diseases and can present to a variety of health care professionals, including teams working in paediatric intensive care. Paediatric intensive care teams can care for the child with ToF pre-operatively, peri-operatively and post-operatively. Each stage of management has its own unique challenges. In this paper we will discuss the role of paediatric intensive care in each stage of management.